Immunization Elicits Antigen-Specific Antibody Sequestration in Dorsal Root Ganglia Sensory Neurons - Gunasekaran, Manojkumar; Chatterjee, Prodyot K.; Shih, Andrew; Imperato, Gavin H.; Addorisio, Meghan; Kumar, Gopal; Lee, Annette; Graf, John F.; Meyer, Dan; Marino, Michael; Puleo, Christopher; Ashe, Jeffrey; et al. (Frontiers in Immunology, 2018)
Abstract The immune and nervous systems are two major organ systems responsible for host defense and memory. Both systems achieve memory and learning that can be retained, retrieved, and utilized for decades. Here, we report the surprising discovery that peripheral sensory neurons of the dorsal root ganglia (DRG) of immunized mice contain antigen-specific antibodies. Using a combination of rigorous molecular genetic analyses, transgenic mice, and adoptive transfer experiments, we demonstrate that DRGs do not synthesize these antigen-specific antibodies, but rather sequester primarily IgG1 subtype antibodies. As revealed by RNA-seq and targeted qPCR, DRG sensory neurons harvested from either naïve or immunized mice lack enzymes (i.e., RAG1, RAG2, AID, or UNG) required for generating antibody diversity, and therefore, cannot make antibodies. Additionally, transgenic mice that express a reporter fluorescent protein under the control of Ig 1 constant region fail to express Ighg1 transcripts in DRG sensory neurons. Further, neural sequestration of antibodies occurs in mice rendered deficient in neuronal Rag2, but antibody sequestration is not observed in DRG sensory neurons isolated from mice that lack mature B cells (e.g., Rag1 knock out (KO) or µMT mice). Finally, adoptive transfer of Rag1-deficient bone marrow into wild-type mice or wild-type bone marrow into Rag1 KO mice revealed that antibody sequestration was observed in DRG sensory neurons of chimeric mice with wild-type bone marrow but not with Rag1-deficient bone marrow. Together, these results indicate that DRG sensory neurons sequester and retain antigen-specific antibodies released by antibody-secreting plasma cells. Coupling this work with previous studies implicating DRG sensory neurons in regulating antigen trafficking during immunization raises the interesting possibility that the nervous system collaborates with the immune system to regulate antigen-mediated responses.